Relationship between dietary antioxidant intake and semen analysis parameters - Safa Gharghanipour; Mahboubeh Taebi; Peyman Salehi; Motahar Heidari-Beni (Mashhad University of Medical Sciences, 2018)
Introduction: Oxidative stress is known as a cause of male infertility. Antioxidants are considered as effective agents against oxidative stress. Regarding this, the present study was conducted to determine the relationship between dietary antioxidants intake and semen analysis parameters. Methods: This descriptive-correlational study was performed on 190 men referring to the Fertility and Infertility Center of Shahid Beheshti in Isfahan, Iran, during 2016-2017. The dietary intakes of antioxidants were obtained by Food Frequency Questionnaire (FFQ) and Nutritionist IV software. After analyzing the semen parameters, data analysis was performed using Mann-Whitney U test and Spearman correlation in SPSS software (version 16). P-value less than 0.05 was considered statistically significant. Results: The mean antioxidant intakes in men regarding vitamins A, E, and C were obtained as 2081.81±1459.47 μg, 5.52±3.55 mg, and 251.63±160.58 mg, respectively. The results showed that the mean amount of received antioxidants (i.e., vitamins A, E, and C) had no significant relationship with sperm analysis parameters, including sperm volume, number, mobility, and morphology, as well as white blood cell count in semen (P>0.05). Conclusion: As the findings indicated, the dietary intake of antioxidants, including vitamins A, E, and C, was not significantly correlated with sperm analysis parameters (i.e., sperm volume, count, motility, and morphology, as well as the number of white blood cells in semen).